The Competition between the US and China for AI Dominance - Meleouni, Christina; Giannou, Christina (HAPSc Policy Briefs Series, 2025)
This article aims to comparatively study the strategic approaches of the two superpowers, in conquering Artificial Intelligence (AI) with a focus on American innovation in private sector leadership, to maintain superiority, relative to the People's Republic of China, and their focus on state-supported projects, merging military and civilian AI applications with strong national policies that also aim at AI superiority. By mapping the context of the technological race for leadership between the United States and the People's Republic of China, this paper will illustrate why the current competition is decisive and characterized primarily by the speed of AI development.